Impact of Website Attributes on Women’s Apparel Purchase Decisions: A Strategic Marketing Perspective - Babima, M.; Kunal, Kishore; Anand, S. T.; Madeshwaren, Vairavel (International Review of Management and Marketing, 2025)
Website attributes such as usability, security, content quality, and design aesthetics play a critical role in shaping women’s apparel purchasing behavior in online retail. This study examines the strategic impact of these attributes on consumer decision-making through data collected via a structured questionnaire using a 5-point Likert scale. Analytical techniques including multiple regression analysis and ANOVA, performed in SPSS, reveal that all proposed hypotheses are supported. Specifically, (1) Design aesthetics positively influence purchase intentions, (2) Usability factors such as mobile responsiveness and intuitive navigation significantly enhance consumer engagement, (3) High-quality content, including detailed product descriptions and authentic reviews, strengthens consumer trust and purchase decisions, and (4) Security features such as secure payment gateways and robust data protection are essential in maintaining customer confidence. The findings underscore that design aesthetics, usability, and content quality have the strongest impact on purchase behavior, while security remains a foundational trust factor. These results offer valuable implications for management and marketing practitioners, highlighting the importance of optimizing e-commerce platforms to enhance customer satisfaction, increase engagement, and drive sustainable sales growth.